Debris Disks and Multiplicity within the 75pc Volume-limited A-Star (VAST) Survey. Issue Volume 8:Issue S299(2013) (6th January 2014) - De Rosa, R. J.; Smith, B.; Bulger, J.; Patience, J.; Marois, C.; Song, I.; Macintosh, B.; Graham, J.; Doyon, R.; Bessell, M.
Abstract: We present the preliminary findings of an investigation of the multiplicity of debris disk stars identified within our Volume-limited A-star (VAST) multiplicity survey. Previous studies have produced conflicting results regarding the multiplicity fraction of debris disk-hosting stars compared with non-excess stars. By combining our large-scale volume-limited AO survey of A-type stars with the all-sky WISE catalogue, we have investigated the frequency of binary companions to a large sample of A-type stars with and without measured 22μm excess. The results of this study will allow for a greater understanding of the interaction between a companion star and a circumstellar debris disk, informing future study into the formation and stability of planetary-mass companions within binary systems.